Anti-static water-based coating for low-absorption high-incidence archery body and preparation method of anti-static water-based coating
By using white conductive zinc oxide and tough water-based resin to prepare a low-absorption, high-emission antistatic water-based coating, the environmental protection and safety issues of the outer surface coating of the rocket have been solved, and the high antistatic performance and weather resistance have been improved, making it suitable for the high temperature and high humidity environment of launch vehicles.
Patent Information
- Application Number
- CN202511051928.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-31
AI Technical Summary
Existing coatings for the outer surface of rockets have environmental and safety issues and cannot effectively prevent the hazards caused by static electricity accumulation. In particular, in high temperature and high humidity environments, the coatings cannot meet the requirements for antistatic performance and weather resistance.
Using white conductive zinc oxide and tough water-based resin as the main components, zinc oxide doped with gallium ions is prepared by chemical co-precipitation to form a core-shell structure. Combined with air spraying process, a low-absorption, high-emissivity antistatic water-based coating is prepared. The coating has an absorptivity of less than 0.25, an emissivity of greater than 0.88, and a volume resistivity of less than 107 Ω·m.
It achieves high antistatic performance on the outer surface of the rocket body, improves the coating's resistance to strong solar radiation and high temperature and humidity environments, and is environmentally friendly and safe, making it suitable for the antistatic requirements of launch vehicles.
Smart Images

Figure CN120865767A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an antistatic coating for rocket bodies, and more particularly to a low-absorption, high-emission antistatic water-based coating for rocket bodies and its preparation method, belonging to the field of antistatic coating technology. Background Technology
[0002] With the development of lightweight launch vehicle systems, non-metallic composite materials are gradually replacing metallic materials as the dominant materials for rocket body structures such as equipment compartments, final repair compartments, and long fairings. The aramid fiber, glass fiber, and other non-carbon-based composite materials extensively used in rocket body structures are insulating materials. When static electricity is generated, it cannot be discharged in time, leading to static accumulation. Since the rocket itself contains a large amount of fuel and various charged instruments and equipment, static electricity accumulation can lead to catastrophic consequences. Among these, electrostatic discharge (ESD) is the most serious and widespread hazard. ESD damage to products mainly manifests as damage to sensitive devices such as semiconductors. ESD can also interfere with the normal operation of electronic equipment: ESD can generate broadband electromagnetic pulse interference with frequencies ranging from hundreds of hertz to tens of megahertz and amplitudes reaching tens of millivolts. This interference can affect the low-level digital circuits of computers and other electrical equipment through various pathways, causing circuit level flipping effects. In addition, it can also cause information loss or functional failure. Furthermore, for high-speed launch vehicles, due to aerodynamic heating, the surface temperature of the launch vehicle rises extremely rapidly. If static electricity cannot be discharged in time, it will lead to serious consequences.
[0003] Therefore, effective anti-static measures must be taken to provide a path for static electricity dissipation, thereby eliminating the potential threats posed by static electricity. Currently, one effective method for preventing static electricity on the outer surfaces of launch vehicles and other spacecraft is to coat them with anti-static coatings. Anti-static performance is one of the essential properties that protective coatings for the outer surfaces of rockets must possess. Generally, the anti-static performance of coatings requires a volume resistivity of less than 10 Ω·cm. 7 Ω·m
[0004] Furthermore, the climate conditions at the newly built Hainan launch site are relatively higher than those at the original Jiuquan launch site, with higher temperatures, humidity, and solar radiation intensity. Therefore, higher requirements are placed on the corrosion resistance, weather resistance, and cold coating effect of the coating system. The Hainan rocket launch site is close to the equator, and the region has a tropical maritime monsoon climate with high solar radiation intensity. During the rocket's parking phase at the launch site, to prevent the rocket from overheating due to solar radiation, the outer surface coating of the rocket body needs to have a low solar absorptivity (α). s and higher infrared emissivity ε N Therefore, the coating used must be a cold coating (α). s / ε N <1), In order to better ensure the temperature control capability of the outer surface coating of the rocket, the solar absorptivity α of the outer surface coating of the rocket is required to be high. s <0.3.
[0005] The protective coatings on the outer surfaces of my country's currently operational rockets generally use epoxy nitrocellulose enamel topcoats, or two-component acrylic and silicone rubber system topcoats. These coatings are all solvent-based, releasing large amounts of volatile organic compounds during production and use, causing environmental pollution and posing potential flammability and explosiveness hazards. To address the environmental and safety issues associated with current rocket outer surface coatings, the demand for water-based rocket body coatings is becoming increasingly urgent. Summary of the Invention
[0006] The purpose of this invention is to overcome the above-mentioned defects and provide a low-absorption, high-emissivity antistatic water-based coating for rocket bodies and its preparation method, solving the technical problem of poor environmental protection and safety of protective coatings on the outer surface of rocket bodies. The coating of this invention has an absorptivity of less than 0.25, an emissivity of greater than 0.88, and an antistatic performance of less than 10. 7 The Ω·m is simple to prepare and improves its ability to withstand strong solar radiation and high temperature and humidity rocket launch site environments, while also improving the antistatic performance of the rocket body.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0008] An antistatic water-based coating for low-absorption, high-emission rocket bodies comprises the following components by mass percentage:
[0009] Coating filler content: 50%–70%;
[0010] The coating film content is 30%–50%.
[0011] The coating filler is white conductive zinc oxide, and the coating film is a tough water-based resin.
[0012] Furthermore, the volume resistivity of white conductive zinc oxide is less than 1 Ω·m, and its solar absorptivity is less than 0.15.
[0013] The impact resistance of the tough water-based resin is not less than 50 kg·cm, and the flexibility is not less than 2 mm.
[0014] Furthermore, the white conductive zinc oxide is zinc oxide doped with gallium ions, prepared by chemical co-precipitation.
[0015] Furthermore, the preparation method of white conductive zinc oxide includes:
[0016] A core-shell structure is formed by coating the surface of zinc oxide powder with a highly doped Ga zinc oxide shell.
[0017] The thickness of the highly doped Ga zinc oxide shell is 1–10 nm, and the mass percentage of Ga in the highly doped Ga zinc oxide shell is greater than or equal to 2%.
[0018] Furthermore, the preparation method of white conductive zinc oxide includes:
[0019] First, ZnSO4·7H2O and a salt solution containing GaCl3 are mixed, and then a saturated NH4HCO3 solution is added as a precipitant to obtain basic zinc carbonate powder containing gallium metal doping.
[0020] The gallium-doped basic zinc carbonate powder was repeatedly washed to remove residual impurities, then dried and ground to obtain gallium-doped zinc oxide.
[0021] Furthermore, the tough waterborne resin includes one or more of waterborne acrylic resins or waterborne polyurethane resins.
[0022] Furthermore, the thickness of the antistatic water-based coating is 50–100 μm.
[0023] Furthermore, the antistatic water-based coating has an absorptivity of less than 0.25, an emissivity greater than 0.88, and an antistatic performance of less than 10. 7 Ω·m.
[0024] The above-mentioned method for preparing an antistatic water-based coating for a low-absorption, high-emission rocket body includes:
[0025] A low-absorption, high-emissivity antistatic coating is formed by uniformly mixing coating filler, coating film-forming agent, water-based additive and deionized water. The low-absorption, high-emissivity antistatic coating is continuously sprayed onto the surface of the substrate using an air spraying process to obtain an antistatic water-based coating.
[0026] Furthermore, the mass percentage of deionized water in low-absorption, high-emission antistatic coatings is 30%-50%.
[0027] Compared with the prior art, the present invention has at least one of the following advantages:
[0028] (1) This invention creatively proposes a low-absorption, high-emission antistatic water-based coating for rocket bodies. The coating absorptivity can be less than 0.25, the coating emissivity can be greater than 0.88, and the coating antistatic performance can be less than 10. 7 Ω·m can be used on the outer surface of the rocket body to improve its ability to withstand strong solar radiation and high temperature and humidity rocket launch site environment, while also improving the antistatic performance of the rocket body;
[0029] (2) The preparation process of this invention is simple and it has potential for wide application in the civilian field;
[0030] (3) The coating of the present invention uses water-based resin as the coating film material, which has high safety and environmental protection. Attached Figure Description
[0031] Figure 1This is a flowchart illustrating the preparation process of the low-absorption, high-emission antistatic coating of the present invention. Detailed Implementation
[0032] The features and advantages of the present invention will become clearer and more apparent from the following detailed description.
[0033] The term “exemplary” as used herein means “serving as an example, embodiment, or illustration.” Any embodiment illustrated herein as “exemplary” is not necessarily to be construed as superior to or better than other embodiments. Although various aspects of embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless specifically indicated otherwise.
[0034] This invention uses a white conductive zinc oxide with a volume resistivity of less than 1 Ω·m and a solar absorptivity of less than 0.15 as a low-absorption, high-emissivity filler, and an water-based resin with an impact resistance of not less than 50 kg·cm and a flexibility of not less than 2 mm as a coating film-forming material. By controlling the coating spraying process, the conductive zinc oxide is uniformly distributed in the coating, achieving an absorptivity of less than 0.25, an emissivity of greater than 0.88, and an antistatic performance of less than 10. 7 The low-absorption, high-emission antistatic coating has a simple preparation process and excellent performance. It can be used on the outer surface of rocket bodies to improve their resistance to strong solar radiation and high-temperature, high-humidity rocket launch site environments, while also enhancing the antistatic performance of the rocket body. In addition, this coating also has potential for wide-ranging applications in the civilian sector.
[0035] This invention provides a low-absorption, high-emission antistatic coating and its preparation method. The preparation process of this low-absorption, high-emission antistatic coating is simple and its comprehensive performance is excellent. It can be used on the outer surface of rocket bodies to improve their ability to withstand strong solar radiation and high-temperature and high-humidity rocket launch site environments, while also improving the antistatic performance of the rocket body. In addition, this coating also has potential for wide application in the civilian field.
[0036] The present invention discloses a low-absorption, high-emission antistatic coating, the components of which are: the coating filler is white conductive zinc oxide, and the coating film is a tough waterborne resin.
[0037] White conductive zinc oxide has a volume resistivity of less than 1 Ω·m and a solar absorptivity of less than 0.15.
[0038] The tough waterborne resin has an impact resistance of not less than 50 kg·cm and a flexibility of not less than 2 mm.
[0039] The white conductive zinc oxide filler in the low-absorption, high-emission antistatic coating contains 50% to 70% by mass, and the tough waterborne resin contains 30% to 50% by mass.
[0040] The thickness of the low-absorption, high-emission antistatic coating is 50–100 μm.
[0041] like Figure 1 A method for preparing a low-absorption, high-emission antistatic coating includes the following steps:
[0042] (1) Preparation of low-absorption-rate zinc oxide conductive powder, the present invention uses Ga 3+ Ga was synthesized using a co-precipitation method as the main cation dopant. 3+ Gallium-doped white zinc oxide conductive powder was prepared by high-temperature solid-state sintering of doped basic zinc carbonate particles. The white conductive zinc oxide has a volume resistivity of less than 1 Ω·m and a solar absorptivity of less than 0.3.
[0043] (2) Using white conductive zinc oxide prepared by the method described in (1) as filler and tough water-based resin as coating film, the white conductive zinc oxide, tough water-based resin, coating additives and appropriate amount of deionized water are stirred, mixed and ground evenly to form a low-absorption high-emission antistatic coating; then the low-absorption high-emission antistatic coating is prepared by continuous spraying on the surface of the substrate using an air spraying process.
[0044] The tough waterborne resin has an impact resistance of not less than 50 kg·cm and a flexibility of not less than 2 mm.
[0045] The white conductive zinc oxide filler in the low-absorption, high-emission antistatic coating contains 50% to 70% by mass, and the tough waterborne resin contains 30% to 50% by mass.
[0046] The thickness of the low-absorption, high-emission antistatic coating is 50–100 μm.
[0047] The deionized water content in low-absorption, high-emission antistatic coatings is 30%-50%.
[0048] The low-absorption, high-emissivity antistatic coating of this invention has the advantages of simple preparation process, antistatic properties, low absorptivity, and high emissivity. Its absorptivity can be less than 0.25, its emissivity greater than 0.88, and its antistatic performance less than 10. 7 Ω·m; Meanwhile, the preparation method of this low-absorption, high-emission antistatic coating has the advantages of simple process and good versatility. It can be used on the outer surface of the rocket body to improve its ability to withstand strong solar radiation and high temperature and humidity rocket launch site environment, while improving the antistatic performance of the rocket body. In addition, this coating also has the potential for wide application in the civilian field.
[0049] Example:
[0050] The present invention discloses a low-absorption, high-emission antistatic coating, the components of which are: the coating filler is white conductive zinc oxide, and the coating film is a tough waterborne resin.
[0051] In one specific embodiment, gallium-doped zinc oxide is prepared by chemical co-precipitation. A highly doped Ga zinc oxide shell several nanometers thick is coated onto the surface of the zinc oxide powder, forming a core-shell structure. By reducing the defect density of the core zinc oxide, high whiteness is obtained. Simultaneously, conductive channels are formed on the surface, resulting in high conductivity, thus alleviating the trade-off between whiteness and conductivity. The white conductive zinc oxide prepared by the above method can have a volume resistivity of less than 1 Ω·m and a solar absorptivity of less than 0.15.
[0052] In one specific embodiment, the impact resistance of the tough waterborne resin is not less than 50 kg·cm and the flexibility is not less than 2 mm.
[0053] In one specific embodiment, the white conductive zinc oxide filler in the low-absorption, high-emission antistatic coating has a mass percentage content of 50% to 70%, and the tough waterborne resin has a mass percentage content of 30% to 50%.
[0054] In one specific embodiment, the thickness of the low-absorption, high-emission antistatic coating is 50–100 μm.
[0055] The above-mentioned method for preparing a low-absorption, high-emission antistatic coating includes the following steps:
[0056] This low-absorption, high-emission antistatic coating uses white conductive zinc oxide as filler and tough water-based resin as coating film-forming material. The white conductive zinc oxide, tough water-based resin, water-based additives, and an appropriate amount of deionized water are stirred and mixed evenly to form a low-absorption, high-emission antistatic coating. Then, the low-absorption, high-emission antistatic coating is prepared by continuously spraying it onto the surface of the substrate using an air spraying process.
[0057] In one specific embodiment, the deionized water content in the low-absorption, high-emission antistatic coating is 30%-50%.
[0058] The technical solution of the present invention will be further illustrated below with various embodiments.
[0059] Preparation of white conductive zinc oxide: First, mix 1 mol ZnSO4·7H2O with a solution containing 0.01 mol GaCl3 salt, then add a 2 mol saturated NH4HCO3 solution as a precipitant to prepare basic zinc carbonate powder doped with gallium metal. Repeatedly wash to remove residual impurities, then dry and grind to obtain gallium metal doped zinc oxide.
[0060] After preparing white conductive zinc oxide, a low-absorption, high-emission antistatic coating was prepared. Specific examples are as follows.
[0061] Example 1
[0062] First, prepare a low-absorption, high-emission antistatic coating with the following raw material ratio: 20g of white conductive zinc oxide, 20g of tough water-based acrylic resin, and 40g of deionized water. Stir, mix, and grind the mixture thoroughly until homogeneous.
[0063] Then, an air spraying process is used to continuously spray the coating to the required thickness range.
[0064] Finally, cure the coating at room temperature for ≥24 hours.
[0065] The low-absorption, high-emissivity antistatic coating has an absorptivity of 0.23, an emissivity of 0.89, and a volume resistivity of 8.3 × 10⁻⁶. 6 Ω·m, coating thickness 50μm.
[0066] Example 2
[0067] First, prepare a low-absorption, high-emission antistatic coating with the following raw material ratio: 25g of white conductive zinc oxide, 15g of tough water-based acrylic resin, and 30g of deionized water. Stir, mix, and grind the mixture thoroughly until homogeneous.
[0068] Then, an air spraying process is used to continuously spray the coating to the required thickness range.
[0069] Finally, cure the coating at room temperature for ≥24 hours.
[0070] The low-absorption, high-emissivity antistatic coating has an absorptivity of 0.22, an emissivity of 0.90, and a volume resistivity of 5.6 × 10⁻⁶. 6 Ω·m, coating thickness 90μm.
[0071] Example 3
[0072] First, prepare a low-absorption, high-emission antistatic coating with the following raw material ratio: 30g of white conductive zinc oxide, 15g of tough waterborne polyurethane resin, and 20g of deionized water. Stir, mix, and grind the mixture thoroughly until homogeneous.
[0073] Then, an air spraying process is used to continuously spray the coating to the required thickness range.
[0074] Finally, cure the coating at room temperature for ≥24 hours.
[0075] This low-absorption, high-emissivity antistatic coating has an absorptivity of 0.22, an emissivity of 0.90, a coating thickness of 80 μm, and a volume resistivity of 2.9 × 10⁻⁶. 6 Ω·m.
[0076] Example 4
[0077] First, prepare a low-absorption, high-emission antistatic coating with the following raw material ratio: 35g of white conductive zinc oxide, 15g of tough waterborne polyurethane resin, and 30g of deionized water. Stir, mix, and grind the mixture thoroughly until homogeneous.
[0078] Then, an air spraying process is used to continuously spray the coating to the required thickness range.
[0079] Finally, cure the coating at room temperature for ≥24 hours.
[0080] The low-absorption, high-emissivity antistatic coating has an absorptivity of 0.21, an emissivity of 0.90, and a volume resistivity of 8.2 × 10⁻⁶. 5 Ω·m, coating thickness 100μm.
[0081] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.
[0082] The contents not described in detail in this specification are common knowledge to those skilled in the art.
Claims
1. A low-absorption, high-emission antistatic water-based coating for rocket bodies, characterized in that, The components include the following mass percentages: Coating filler content: 50%–70%; The coating film content is 30%–50%. The coating filler is white conductive zinc oxide, and the coating film is a tough water-based resin.
2. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, The volume resistivity of white conductive zinc oxide is less than 1 Ω·m, and its solar absorptivity is less than 0.
15. The impact resistance of the tough water-based resin is not less than 50 kg·cm, and the flexibility is not less than 2 mm.
3. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 2, characterized in that, The white conductive zinc oxide is zinc oxide doped with gallium ions, prepared by chemical co-precipitation.
4. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, Methods for preparing white conductive zinc oxide include: A core-shell structure is formed by coating the surface of zinc oxide powder with a highly doped Ga zinc oxide shell. The thickness of the highly doped Ga zinc oxide shell is 1–10 nm, and the mass percentage of Ga in the highly doped Ga zinc oxide shell is greater than or equal to 2%.
5. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, Methods for preparing white conductive zinc oxide include: First, ZnSO4·7H2O and a salt solution containing GaCl3 are mixed, and then a saturated NH4HCO3 solution is added as a precipitant to obtain basic zinc carbonate powder containing gallium metal doping. The gallium-doped basic zinc carbonate powder was repeatedly washed to remove residual impurities, then dried and ground to obtain gallium-doped zinc oxide.
6. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, Tough waterborne resins include one or more of waterborne acrylic resins or waterborne polyurethane resins.
7. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, The thickness of the antistatic water-based coating is 50–100 μm.
8. The antistatic water-based coating for a low-absorption, high-emission rocket body according to claim 1, characterized in that, The antistatic water-based coating has an absorptivity of less than 0.25, an emissivity greater than 0.88, and an antistatic performance of less than 10. 7 Ω·m.
9. A method for preparing a low-absorption, high-emission antistatic aqueous coating for a rocket body according to any one of claims 1-8, characterized in that, include: A low-absorption, high-emissivity antistatic coating is formed by uniformly mixing coating filler, coating film-forming agent, water-based additive and deionized water. The low-absorption, high-emissivity antistatic coating is continuously sprayed onto the surface of the substrate using an air spraying process to obtain an antistatic water-based coating.
10. A method for preparing an antistatic aqueous coating for a low-absorption, high-emission rocket body according to claim 9, characterized in that, The mass percentage of deionized water in low-absorption, high-emission antistatic coatings is 30%-50%.